2015
DOI: 10.1038/nmeth.3351
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing small genomic targets with high efficiency and extreme accuracy

Abstract: The detection of minority variants in mixed samples demands methods for enrichment and accurate sequencing of small genomic intervals. We describe an efficient approach based on sequential rounds of hybridization with biotinylated oligonucleotides, enabling more than one-million fold enrichment of genomic regions of interest. In conjunction with error correcting double-stranded molecular tags, our approach enables the quantification of mutations in individual DNA molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
137
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(146 citation statements)
references
References 24 publications
4
137
1
1
Order By: Relevance
“…dNTP pools | colon cancer | DNA replication fidelity R ecent advances in whole-genome sequencing have revealed that human cancers often contain thousands of subclonal mutations (1)(2)(3), lending support to the mutator phenotype hypothesis that postulates that an elevation in spontaneous mutation rate is an early step in cancer evolution (4,5). The three major determinants of DNA replication fidelity that control the spontaneous mutation rate are nucleotide selectivity by DNA polymerases, proofreading by replicative DNA polymerases, and the mismatch repair (MMR) system (6).…”
mentioning
confidence: 99%
“…dNTP pools | colon cancer | DNA replication fidelity R ecent advances in whole-genome sequencing have revealed that human cancers often contain thousands of subclonal mutations (1)(2)(3), lending support to the mutator phenotype hypothesis that postulates that an elevation in spontaneous mutation rate is an early step in cancer evolution (4,5). The three major determinants of DNA replication fidelity that control the spontaneous mutation rate are nucleotide selectivity by DNA polymerases, proofreading by replicative DNA polymerases, and the mismatch repair (MMR) system (6).…”
mentioning
confidence: 99%
“…An important consideration when designing a selector is that sequencing cost is proportional to the size of the region being sequenced. It should be noted, that targeting very small regions is associated with its own hurdles because the enrichment efficiency of a single capture are typically on the order of 10 4 -fold, so for the targets smaller, than approximately 100 kb additional steps, such as two rounds of capture may be necessary to ensure sufficiently high on-target mapping rate (82). For patient-specific applications or cancers with a high mutation rate (or recurrence in a small number of genes), this may allow deep sequencing to be achieved at a low cost using "bench-top" NGS devices.…”
Section: Ligation and Hybridization-capture Methodsmentioning
confidence: 99%
“…For example, the authors of one of such approach, Schmitt and colleagues estimated the error rate of 3.8 Â 10 À10 in a model experiment (88). The same group demonstrated the robustness of their approach by detecting a single ABL1 imatinib conferring mutation in a sample from the chronic myeloid leukemia patient (82). The E279K mutation was unambiguously detected at 1% rate, whereas the error rate of raw sequencing data would have either completely or partially obscured this mutation.…”
Section: Error Suppression Methodsmentioning
confidence: 99%
“…This internal error correction effectively reduces false positive mutations because PCR and sequencing artifacts are very unlikely to occur at both strands of DNA at the same position and with complementary nucleotide changes (theoretical false positive rate is ∼4 × 10 −10 ) (7). Previous studies have demonstrated that duplex sequencing is able to detect a single point mutation among >10 7 sequenced nucleotides (7,8), an unprecedented accuracy that holds significant potential for early cancer detection.High-grade serous ovarian carcinoma (HGSOC) is the most common and most aggressive type of ovarian cancer, with a dismal 5-y survival rate of 10-30% (9). A main cause of poor prognosis is the absence of effective screening tools to detect early-stage disease.…”
mentioning
confidence: 99%
“…Moreover, >95% of TP53 mutations cluster in exons 4-10 (15), which provides a relatively small target to perform cost-efficient ultra-deep sequencing (8). Thus, we used duplex sequencing to sequence TP53 exons 4-10 in peritoneal fluid from patients with HGSOC with known TP53 mutations and control patients without ovarian cancer.…”
mentioning
confidence: 99%